The influence of social networking sites on student involvement on campus among Islamic University students - Htwe, Myint (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This study investigates the influence of social networking sites (SNSs) on student involvement on campus among Islamic university students in Malaysia. The objectives of the study are to find out: (1) the characteristics of SNS users; (2) the SNS usage and motives; (3) the level of satisfaction with life and student involvement; (4) the influence of SNS motives on student involvement, intensity of SNS usage and satisfaction with life; (5) the influence of intensity of SNS usage and satisfaction with life on student involvement; (6) the mediations of intensity of SNS usage and satisfaction with life on the relationships between SNS motives and student involvement; and (7) to develop a model for SNS motives and student involvement. There is limited empirical research on the effects of social networking sites on individuals and society. This study intends to fill the gap in the literature by employing Uses and Gratifications theory. Using a cross-sectional survey method, a self-administered questionnaire was used. A total of 368 Muslim undergraduate students from two Islamic universities, IIUM and USIM in Malaysia, were respondents of the study. Structural equation modeling (SEM) and other relevant statistical techniques were used to analyse the data to achieve the main objectives and to test the hypotheses of the study. Results show that religious motive is the best predictor of student involvement among Islamic university students while information motive strongly predicts the intensity of SNS usage. In addition, information and religious motives are significant predictors of satisfaction with life, which is positively correlated with student involvement. It also shows that the relationship between social interaction motive and student involvement is fully mediated by satisfaction with life. Results are discussed in terms of theoretical and practical implications as well as directions for future research.